ANALYSING THE BOTTLENECKS IN LAUNDRY SERVICE OPERATION USING CAUSE AND EFFECT DIAGRAM (CASE STUDY ON FRESH & CLEAN COIN LAUNDRY IN MANADO) - Sinsu, Eirene E.; Pangemanan, Sifrid S. (Universitas Sam Ratulangi, 2018)
Abstract: Fresh & clean coin laundry experienced the complaint from customer because delay in completion the customer laundry as the promised time. The slowdown of the operation processes usually happens because there are bottlenecks. Figuratively, bottleneck refers to any obstruction that slows down a flow or process. The aims of this research is to identify and analyze the causes of the bottlenecks in laundry service operation of Fresh & clean coin laundry. This research is descriptive research and uses qualitative method. Based on the result, this research is found 15 possible causes of the laundry service operation slowdown by using cause and effect diagram and than by using pareto analysis it is found that there is 2 significant causes that cause the bottlenecks in laundry service operation which is Fewer Steam Ironswith 24% causes contribution and Fewer Coin Laundry Machine is 21%. So these two causes are responsible for 45% of total causes of laundry service operation slowdown. Fresh & clean coin laundry needs to add more steam irons and coin laundry machine because the causes of delay to completion the customer laundry as the promised time is because there is bottlenecks in ironing and washing workstation that limiting the output.Keywords: service operation, bottlenecks, cause and effect diagram, pareto analysis.